The Effect of Using a physical Rehabilitation Training Program for Injured Shoulder Joint Muscles on the Development of Spiking in Sitting Volleyball Players - sabhan, Husein (Journal of Physical Education, 2012)
Most sitting volleyball movements and skills are executed using arm support and pushing with them forwards, backwards and side wards. Thus, most of the effort lies on shoulder joint muscles and the arms of players during performing volleyball movements and skills specially spiking. The importance of the study lies in designing a training program for rehabilitating shoulder joint muscles to develop the performance of spiking in sitting volleyball players.The aim of the research is to identify the effect of this training program in rehabilitating shoulder joint muscles and developing spiking in sitting volleyball players. The researcher used the experimental method. The subjects were (5) national sitting volleyball league players with shoulder muscle’s injury.The researcher came up with many results yet the most important result was that using light weights and stability exercises are very effective in strengthening and rehabilitating injuries joint muscles. In addition to that, the training program increased and developed shoulder working muscles and the range of motion of the joint. This development led to a great gain in shoulder function. Finally, the training program led to the development of spiking skill in sitting volleyball players.Finally the researcher recommended the necessity of paying attention to strengthening shoulder muscles for sitting volleyball players to avoid injuries during performing volleyball skills especially spiking. In addition to that, the researcher recommended putting ice on the injured area after training because it decreases pain and contracts blood vessels. Coaches should concentrate on full warm up before any training to keep the body safe from injuries. Players should guided on how to react during sudden injury like falling on the ground correctly instead of falling on their arms. Finally, the researcher recommended using general physical exercises hat can be performed every where and at any time like push ups to strengthen shoulder muscles